Eco-friendly feed innovation: An effective strategy to reduce fish mortality rates in Central Bangka - Priyansah, Sujadi; Dalimunthe, Nurzaidah Putri; Sembiring, Juhardi; Arif, Maulana; Kurnia, Feni; Syafutra, Randi; Adibrata, Sudirman; Lingga, Rahmad (Community Empowerment, 2025)
Former tin mining land (known locally as camoy or kulong) has the potential to be utilized as fish cultivation land. Kulong possesses potential for fish farming due to its age, which supports the availability of trophic minerals essential for fish life. Fish farmers frequently encounter problems with disease outbreaks and mortality caused by pathogens, leading to low production yields. Improving the quality of the cultivation environment, including reducing sedimentation from commercial feed, is one solution to mitigate fish diseases and mortality. This community service aims to provide training on environmentally friendly feed for fish farmers through training and mentoring in its application. The program successfully enhanced the partners' ability to produce cost-effective (organic) environmentally friendly feed from agricultural waste (oil palm kernel meal, dregs, bran), which demonstrably improved the quality of the cultivation environment, reduced fish diseases and mortality, and has the potential to increase the quality and quantity of fish production.